Black Garlic: an Innovative Additive for Food Formulations - Carlo Orefice; Nicolina Morganella; Marianna Gallo; Isidoro Garella; Antonio Marzocchella; Roberto Nigro (Chemical Engineering Transactions, 2022)
Black garlic (BG) can be found on menus everywhere, but this unique ingredient isn’t anything new. Traditional and natural BG is, simply put, the product of aging regular garlic bulbs leaving them for weeks and months at typical ambient temperatures and high humidity (about 40°C and 90-100% RH) without addition of any preservatives achieving its typical colour and sticky texture. In this work, in order to speed up the complex Maillard reactions at the base of the organoleptic, textural and nutritional characteristics of the BG. The optimal process conditions and time were determined and the time of the browning of the cloves have been reduced considerably; the tests to produce black garlic are carried out with different temperature values (70-80-90°C) and different relative humidity values (70-80-90% RH). The process time can be consistently reduced ranging between 2-4 days. Samples produced at higher temperature (90°C) and low humidity (70%RH) were dry, friable and with low content of water while samples produced at high humidity (80-90%RH) and low temperature presented a gum-like consistency. The allicin has been totally transformed by the treatment losing the typical smell of the garlic. Moreover, there is also an increasing of the polyphenols and flavonoids contents if compared to the raw fresh garlic (respectively ranging between 32 -26 and 18 -13 mgGAE/gdr). Higher fructose content (250÷ 500 mg / g dry) - that confers sweetness - was measured at the end of the thermal processing as a possible consequence of the hydrolysis of long chain of the fructans.